Efektifitas Video Company Profile Rumah Sakit terhadap Persepsi Pengunjung - Siskha Handayani; Andre Maulana; Rina Yulius (MULTINETICS, 2025)
Embung Fatimah Regional General Hospital (RSUD) Batam City as a health service provider faces the challenge of understanding how the use of visual media can affect visitors' perceptions regarding the services provided. In addition to the quality of the hospital's medical services, the hospital's ability to communicate to itself can also affect visitors' perceptions. The use of multimedia technology, especially through company profile videos, has a central role in communication and marketing strategies in health service institutions. The relevance of the RSUD Embung Fatimah company profile video to the current condition and identity of the Embung Fatimah Regional General Hospital is still inadequate. Therefore, it is necessary to review and update the video content to ensure that the information conveyed is in accordance with the latest developments. This study aims to determine the effectiveness of the company profile video on the perceptions of visitors to the Embung Fatimah Regional General Hospital in Batam City. The Luther Sutopo Model approach was applied in designing the video and the EPIC Model in analyzing its effectiveness. The test results showed that the video that had been developed was very feasible to be distributed with a value of 98%. Meanwhile, in the beta test, it was found that the Embung Fatimah Hospital company profile video had an effectiveness level with an Epic Rate value of 4,130, which was categorized as 'Effective'. So it can be stated that this product is effective in influencing visitors' perceptions of current relevance